Pharmacotherapy during pregnancy, childbirth and lactation: points and principles to consider (a 2015 update) - G. Schellack; N. Schellack; M. Kriel (South African Family Practice)
Pregnancy, childbirth and lactation pose unique challenges in terms of drug therapy. The pregnant mother and her unborn child are exceptionally vulnerable from a physiological, clinical and ethical standpoint. This warrants careful consideration with respect to a number of important aspects, which could firstly influence the decision to opt for drug therapy, and secondly, could influence the specific agent selected for each indication. The US Food and Drug Administration has introduced changes to the content and format of information presented in prescription drug labelling to assist healthcare providers when assessing benefit versus risk, and in the subsequent counselling of pregnant woman and nursing mothers who need to take medication. This change came into effect at the end of June 2015. This article provides an overview of these important aspects.